(untitled) (Indian Journal of Animal Production and Management, 2025)
The paper presents the livestock production scenario of the post-independence India and outcome of several efforts to increase the contribution of livestock sector to the national GDP requiring the emergence of the applied subject Livestock Production Management. The aim of this subject is increased and economic production from livestock sector. Theme of Livestock Production Management is judicious decisions on the use of scarce farm resources, having alternative uses to obtain the maximum profit and family satisfaction on a continuou basis. It further elaborates the evolution of this science and presents a critical analysis of the domain of this subject. A picture is available from this paper as to how knowledge of other subjects is required to achieve the aim of this subject.